Confrontando-se com o próprio trabalho : um estudo interacionista sociodiscursivo sobre o gênero profissional de professoras de inglês do IFPB - Pereira, Marcia de Albuquerque (2016)
Anchored in Applied Linguistics and in interpretive principles, this research aims to investigate the constitution of the teaching professional genre based on (re)configurations made by English teachers from Instituto Federal da Paraíba (IFPB) about their own work. For reaching this goal, two main theoretical spheres are fundamental. The first one is the history of foreign language teaching in professional education that dates from the introduction of English for Specific Purposes (ESP) teaching in Brazil (CELANI, 2009; RAMOS, 2009), in which context lies the English language teaching in IFPB. The second one concerns to the investigation of teaching work through discourse under the fields of Sociodiscursive Interactionism - SDI (BRONCKART, 1999, 2006, 2008; MACHADO & BRONCKART, 2009) associated to studies in Labour Sciences (AMIGUES, 2004; FAITA, 1996; CLOT & FAITA, 2010 [2000]). The SDI also offers a support for linguistic-discursive analysis and, in this research, we emphasize the analysis of theme and enunciation mechanisms, i.e., voices, person marks and modalization (BRONCKART, 1999; MACHADO and BRONCKART, 2009). In order to investigate the professional genre of activity “English teachers from IFPB” we undertake simple self-confrontation, a procedure developed by work scientists (FAÏTA, 1996; CLOT and FAÏTA, 2010 [2000]). Our research participants are five English teachers from different IFPB campuses. In our analysis, the most recurrent themes allowed us to verify that the teachers focused their evaluations on their own selves, on their work and on their work in IFPB. In the evaluations of themselves, they emphasized reflections on physical and subjective aspects, which allowed the verification of collective and subjective dimensions of the genre of the teaching activity. The evaluations on their own work consists on: the judgments about previous experiences that compose the prescriptive dimension of the professional genre; the (in) experiences in IFPB that reveal the situated, subjective and directed dimensions of the teaching work genre; and the reformulations of their own work that reveal the transitory dimension of this professional activity. The evaluations of the work in IFPB reveal that the working tools show the instrumental, prescriptive and cultural genre dimensions and the work object uncovers the cultural dimensions of the teaching activity genre. The stylistic dimension permeates the activity of teachers, once we know that in all teaching activity there is a subjective variation of the genre. The themes and the genre dimensions identified indicate that English teaching in professional education consists mainly in the English for Specific Purposes (ESP) approach, in the molds of the practices implemented in Brazil in the 1970’s. There is, thus, a dissonance between what typifies this kind of activity genre and the needs of the current teaching situation.